STUDI KOMPARATIF AKSES DUKUNGAN SOSIAL DALAM DESAIN RUANG TUNGGU KLINIK ANAK DI RUMAH SAKIT - Abednego Trianto Kurniawan; Agung Dwiyanto (Tesa Arsitektur, 2026)
Hospital design plays a crucial role in children’s well-being, especially in pediatric waiting rooms where prolonged wait times can lead to increased stress and anxiety. However, the spatial design that encourages social interaction in Indonesian children’s healthcare facilities remains largely unexplored. This study aims to investigate how architectural design facilitates access to social support in pediatric outpatient waiting rooms, utilizing the Supportive Design Theory as a guiding framework. A descriptive comparative method was employed to analyze two case studies: SMC Telogorejo Children’s Clinic in Semarang and Pantai Indah Kapuk Women and Children’s Center Hospital in Jakarta. Field observations and photographic documentation analysis were conducted to gather data. The findings revealed several design criteria that enhance social interaction, such as family-centered waiting rooms with visual connectivity between zones, the provision of play areas, proximity to supporting facilities, healing gardens, and rest areas. These elements align with supportive design principles that promote interaction, supervision, and rest, ultimately contributing to the comfort and well-being of children and their families.1.